Recombinant Antibodies in Veterinary Medicine: An Update - Bustamante-Córdova, Lorena; Melgoza-González, Edgar A.; Hernández, Jesús (Frontiers in Veterinary Science, 2018)
The production of recombinant antibodies has had a tremendous impact on several research fields, most prominently in biotechnology, immunology and medicine, enabling enormous advances in each. Thus far, a broad diversity of recombinant antibody (rAb) forms have been designed and expressed using different expression systems. Even though the majority of rAbs approved for clinical use are targeted to humans, advances in veterinary medicine seem promising. The aim of this mini-review is to present an update regarding the rAbs in veterinary medicine reported to date, as well as their potential use in diagnostics, prophylaxis and therapeutics. Full- and single-chain fragment variables are the most common forms of rAbs developed for the detection, prevention and control of parasitic, bacterial and viral diseases, as well as pain and cancer treatment. Nonetheless, advances in research seem to be skewed toward economically important animals, such as pigs, cows, poultry and dogs. Although significant results have been obtained from the rAbs reported here, most have not been developed enough to be approved. Further research and clinical trials should be encouraged to enable important findings to fulfill their intended potential to improve animal well-being.